2015
DOI: 10.1002/mabi.201500107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Microtopography Engineered by Direct Laser Interference for Bacterial Anti-Biofouling

Abstract: Modification of the biomaterial surface topography is a promising strategy to prevent bacterial adhesion and biofilm formation. In this study, we use direct laser interference patterning (DLIP) to modify polystyrene surface topography at sub-micrometer scale. The results revealed that three-dimensional micrometer structures have a profound impact on bacterial adhesion. Thus, line- and pillar-like patterns enhanced S. aureus adhesion, whereas complex lamella microtopography reduced S. aureus adhesion in static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 43 publications
(67 reference statements)
2
52
0
Order By: Relevance
“…On the other hand, complex 3-D patterns (lamella-like) prevented biofilm formation [45]. Similar results were achieved by Valle et al, who showed that pillar and line topographies produced via DLIP increase bacteria adhesion to polymers compared to non-patterned samples, while more irregular and complex lamellar topography reduced adhesion [46]. Furthermore, Langheinrich et al studied cell growth behavior over polyimide patterned with substrates using DLIP to fabricate line-like arrays, showing that the cells aligned to the pattern direction, i.e., they sensed and responded to the change of topology induced by the laser patterning.…”
Section: Direct Laser Interference Patterningsupporting
confidence: 72%
“…On the other hand, complex 3-D patterns (lamella-like) prevented biofilm formation [45]. Similar results were achieved by Valle et al, who showed that pillar and line topographies produced via DLIP increase bacteria adhesion to polymers compared to non-patterned samples, while more irregular and complex lamellar topography reduced adhesion [46]. Furthermore, Langheinrich et al studied cell growth behavior over polyimide patterned with substrates using DLIP to fabricate line-like arrays, showing that the cells aligned to the pattern direction, i.e., they sensed and responded to the change of topology induced by the laser patterning.…”
Section: Direct Laser Interference Patterningsupporting
confidence: 72%
“…Images from confocal microscopy of PS polymeric surfaces structured by DLIP technique. Periodic arrays of (a) linelike (LN) with P = 5 µm, (b) pillar-like (PL) with P = 5 µm, and (c) lamella-like (LA) structures with P = 2 µm [30] .…”
Section: Design Of Patterned Surfaces By Dlipmentioning
confidence: 99%
“…Topographical modification of the resultant surfaces with nano-and microstructures has emerged as a potential tool for the fabrication of functionalized surfaces with antibacterial properties [100]. Some of the technologies usually applied for fabrication of antibacterial surfaces via surface micro-and nanostructuring are chemical etching (Black Silicon), physical vapor deposition (PVD), plasma irradiation, hydrothermal treatments, photolithography, electron-beam lithography and ablation by ultrashort pulsed lasers [101][102][103][104][105][106][107]. In Table 4, the advantages and disadvantages of these micro and nano-patterning technologies are shown.…”
Section: Biocide Surface Treatmentsmentioning
confidence: 99%